Association of nonverbal coordination quality and therapeutic alliance in mentalization-based treatment for children (MBT-C) - Epözdemir, Şevin (İstanbul Bilgi Üniversitesi, 2024)
Çocuklar ve terapistler arasındaki terapötik ittifak, terapinin etkililiği açısından önemli bir unsurdur. İttifak kavramı, terapi görevlerini yerine getirmek için işbirliği kurmayı, terapist ile bağ kurmaya ilişkin duygusal yönleri içerir. Bu çalışma terapistin sözdışı koordinasyon kalitesi ile çocuğun ittifak kopukluğu anları arasındaki ilişkiyi incelemektedir. İttifak kopuklukları çocuğun çatışmaya yönelik veya kendi içine çekildiği davranışlar üzerinden kendini gösterir. Bu çalışma, klinik problemleri olan okul çağındaki çocukların ittifağı ile terapistlerin sözdışı koordinasyonunun ilişkisini anlamaya yönelik ilk araştırmalardan biri olacaktır. Bu çalışmanın bir diğer amacı da çocuk psikoterapisinde kırılma anlarını araştırmaktır. Düşük ittifaklı olarak gözlemlenmiş seanslarda terapistlerin sözdışı koordinasyon kalitesinin çocukların kopmalarının azalmasını yordayacağı varsayılmıştır. Bu nedenle betimsel analiz yapılmıştır. Tüm seans örnekleminden düşük ittifaklı olan seanslar belirlendi. Bu seanslar içe yönelim, dışa yönelim veya komorbid problemleri olan 5-12 yaş arası 28 çocuğun seanslarıydı. Belirlenen seanslar Therapy Process Observational Coding System-Alliance (TPOCS-A), Rupture Resolution Rating System (3RS) ve Therapist's Body Coordination in Child Psychotherapy Coding System ile kodlandı. Hiyerarşik Lineer Modelleme analizleri yapıldı. Analizler, terapistlerin sözdışı koordinasyon kalitesinin farklı kopma türleri ile farklı ilişkilere sahip olduğunu gösterdi. Terapistin sözdışı koordinasyon kalitesi ile çocuğun çatışmaya dayalı kopmaları arasında pozitif bir ilişki bulundu. Terapistin sözdışı koordinasyon kalitesi ile içe dönme kopmaları arasında anlamlı bir ilişki bulunmadı. Bu bulgular, terapistlerin sözdışı koordinasyonunun çocukların daha ilişkisel ve ifade edici olmalarını sağlayabileceğini düşündürdü. Bulgulara ilişkin olası açıklamalar tartışıldı. Anahtar kelimeler: Sözdışı Koordinasyon, Terapötik İttifak, Kırılma, Çocuklara Yönelik Zihinselleştirme Temelli Terapi, Çocuk Psikoterapisi

Therapeutic alliance is an important element for therapy's effectiveness. The concept of alliance includes agreement on therapy tasks and creating a secure bond. The nonverbal aspects of the therapy relationship, such as bodily coordination of the therapeutic dyad is a predictor of therapeutic alliance in adult psychotherapy; however, this has not been studied in child therapies. Current research will be the first to analyze the nonverbal coordination of therapists with children and assess its impact on ruptures, which are moments in the therapy relationship when there is a weakening of the therapeutic bond. This can manifest itself in terms of the patient's confrontative or withdrawing attitudes. It was hypothesized that the therapists' nonverbal coordination quality will predict a decrease of children's rupture salience when the global alliance of the sessions was low. The sample consisted of 28 children between 5-12 years old who have internalizing, externalizing or comorbid problems. These children received Mentalization-Based Treatment for Children (MBT-C), in the context of a randomized controlled trial (RCT) conducted at Istanbul Bilgi University. Three sessions from each child's treatment were coded with Therapy Process Observational Coding System-Alliance Scale (TPOCS-A), Rupture Resolution Rating System (3RS), and Therapist's Body Coordination in Child Psychotherapy Coding System. Hierarchical Linear Modeling analyses were carried out. The results demonstrated that nonverbal coordination quality of therapists have different associations with the salience of different rupture types. There was a positive relationship between therapist's nonverbal coordination quality and child's moving against rupture salience. There was no significant relationship between therapist's nonverbal coordination quality and moving away rupture salience. These findings suggest that therapists' nonverbal coordination may provide children to be more expressive about their confrontative attitude. Possible explanations regarding these associations were discussed. Keywords: Nonverbal Coordination, Therapeutic Alliance, Rupture, Mentalization Based Therapy for Children, Child Psychotherapy
Çocuklar için zihinselleştirme temelli terapi'de sözdışı koordinasyon ve terapi ittifağı ilişkisi
Keywords: Psikoloji; Psychology